2022
DOI: 10.18502/jfrh.v16i4.11351
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Paternal Postpartum Depression in Anuradhapura District in Sri Lanka and its Association with Maternal Postpartum Depression as a Risk Factor

Abstract: Objective: This study aimed to determine the prevalence of PPPD in Anuradhapura district, its association with maternal PPD, and relevant risk factors. Materials and methods: Cross sectional study was conducted among fathers in Anuradhapura district having infants 1-5 months by giving questionnaire specifically developed for the study with Edinburgh postnatal depression scale (EPDS) and self-constructed questions. Out of 6324 fathers, 435 fathers and their partners were randomly selected and proportionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The higher prevalence rates of PND were observed within the 3 months of childbirth (19.26%) in this study and the finding was consistent with a systematic review and metaanalysis conducted in China (28.7%) 39 and inconsistent with study findings of Paulson and Bazemore, they reported higher prevalence rates of PND during 3 to 6 months of postpartum. 3 The pooled prevalence of PND in fathers for studies conducted in institutional-based setting was 19.46% and for community setting it was 13.49%.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The higher prevalence rates of PND were observed within the 3 months of childbirth (19.26%) in this study and the finding was consistent with a systematic review and metaanalysis conducted in China (28.7%) 39 and inconsistent with study findings of Paulson and Bazemore, they reported higher prevalence rates of PND during 3 to 6 months of postpartum. 3 The pooled prevalence of PND in fathers for studies conducted in institutional-based setting was 19.46% and for community setting it was 13.49%.…”
Section: Discussionsupporting
confidence: 67%
“…38 A systemic review and meta-analysis involving 14 studies with 3,819 participants found that the estimated prevalence of PND in fathers was 16.8% when self-rating scales were used to measure PND and 4.1% when interview-based method was used. 39 In the subgroup analysis, the pooled prevalence of PND among fathers in India was found to be 19.41% that was relatively higher than the estimated prevalence of PND among fathers in China (13.6%) 39 and surpasses the worldwide estimated prevalence of PND in fathers. 3,4,38 However, the estimated prevalence of PND in India was lower than Saud Arabia and Iran.…”
Section: Discussionmentioning
confidence: 85%